THE CONCEPT OF ECOTOURISM AND ITS TYPES - Xasanova Nargiza Athamovna; Olimboyev Fazliddin Bahodir o‘g‘li (Web of Journals Publishing, 2024)
In this article, an understanding of the modern methods of ecotourism development in Uzbekistan, prospects for the development of ecotourism and the goal of ecotourism development is given. Also, the article examines the concept and types of ecotourism and reveals their interrelationships.
Keywords: ecotourism, manager, marketing, reserve, resorts, environmental sustainability, sustainable tourism.